2001
DOI: 10.1046/j.1365-2958.2001.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacteriophage φ29‐encoded protein p16.7: a membrane protein involved in phage DNA replication

Abstract: SummaryAn early expressed operon, located at the right end of the linear bacteriophage f29 genome, contains open reading frame (ORF)16.7, whose deduced protein sequence of 130 amino acids is conserved in f29-related phages. Here, we show that this ORF actually encodes a protein, p16.7, which is abundantly and early expressed after infection. p16.7 is a membrane protein, and the N-terminally located transmembrane-spanning domain is required for its membrane localization. The variant p16.7A, in which the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 67 publications
10
77
0
Order By: Relevance
“…All the proteins appeared to have a similar heterogeneous pattern of localization that was strikingly different from the distribution of total membrane when observed with the membrane stain FM4-64. The localization pattern for p16.7 has previously been reported and described as being similar to that of FM4-64 (Meijer et al, 2001). Indeed, in this work we used the same strain, 110WA, to observe p16.7 localization.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…All the proteins appeared to have a similar heterogeneous pattern of localization that was strikingly different from the distribution of total membrane when observed with the membrane stain FM4-64. The localization pattern for p16.7 has previously been reported and described as being similar to that of FM4-64 (Meijer et al, 2001). Indeed, in this work we used the same strain, 110WA, to observe p16.7 localization.…”
Section: Discussionsupporting
confidence: 77%
“…In the absence of other phage proteins, p16.7 is simply a small integral membrane protein with no known role in B. subtilis physiology. The localization of a p16.7-GFP fusion has been previously reported and shown to be confined to the cytoplasmic membrane in a pattern very similar to FM4-64 (Meijer et al, 2001). However, we found that the p16.7-GFP localization pattern was indistinguishable from that of either SdhA-GFP or AtpA-GFP (Fig.…”
Section: Heterogeneous Localization Of Integral Membrane Proteinssupporting
confidence: 82%
See 3 more Smart Citations